APLICAÇÃO DE TIAMINA NA CULTURA DO FEIJÃO - ARAUJO, Adrielly Patrícia Batista; BORTOLHEIRO, Fernanda Pacheco de Almeida Prado Bortolheiro; VENDRUSCOLO, Eduardo Pradi; NETO, Joaquim Tenório; ROCHA, Alana Silva; NASCIMENTO, Ana Carolina Vidal do (ANAIS DO ENIC, 2025)
-